Peran Orang Tua Dalam Mengatasi Masalah Kenakalan Remaja Ditinjau Dari UU Nomor 35 Tahun 2014 Tentang Perlindungan Anak (Studi Kasus di Desa Pematang Johar Kecamatan Labuhan Deli) - Ahmad Irfan; Akmaluddin Syahputra (UNES Law Review, 2023)
Adolescence is a transition period from childhood to adulthood. During this period, many changes occur in teenagers, starting from the physical, knowledge, psychological, and moral and social dimensions. Juvenile delinquency is an act committed by teenagers that violates the laws and norms that apply in society so that it harms their parents, other people, disturbs the peace of society, and harms themselves. This research aims to determine the role of parents in overcoming the problem of juvenile delinquency in terms of Law Number 35 of 2014 concerning child protection in Pematang Johar Village, Labuhan Deli District. This research is a case study using interview, observation and documentation techniques, accompanied by books, journals and other related sources. The results of this research show: that the role of parents in dealing with juvenile delinquency is that parents must be the most important role for children by educating children from an early age by teaching Islamic religious values, for fathers to carry out morning prayers with their children at school. mosque, in the afternoon parents are taking their children to the TPA, sending their children to Islamic boarding schools and youth mosques, in the evening of Muharram parents register their children to take part in competitions at the mosque, send their children to training sports, entering a drug rehabilitation center for those affected by drugs, being a role model for children regarding good words, attitudes and actions at home and outside the home environment, being a counselor or supervisor for children, acting as a good communicator to children, being patient in educate children and always pray so that children become individuals who fear Allah SWT.